ROLE RELATIONSHIP ENACTMENT BETWEEN ENGLISH NON-NATIVE SPEAKERS IN AN ENGLISH DIALOGUE - Sunardi Sunardi (LITE: Jurnal Bahasa, Sastra, dan Budaya, 2009)
This study aims at describing the enactment of role relationships between English non-native speakers in an English dialogue. The speakers are an Indonesian student and a Dutchman who met by accident in a public place in Semarang. The dialogue was analyzed by describing the clause and speech function productions by the speakers. The result of the study shows that in an equal turn right to talk the Dutchman performs as the dominant speaker, while the Indonesian Student as the marginal one. The Indonesian student plays the role of interaction stirrer by dominating the opening speech functions with questions. On the other hand, the Dutchman plays the role of interaction supporter by dominating the continuing and responding speech functions. The lack of confrontational speech functions by the speakers in this dialogue is probably caused by the low contact between them, since it is their first time of face-to-face meeting.Key words: role relationship, speech function, dominant speaker,marginal speaker